The evolution of the galaxy UV luminosity function at redshifts z ≃ 8 – 15 from deep JWST and ground-based near-infrared imaging. Issue 4 (21st November 2022) - Donnan, C T; McLeod, D J; Dunlop, J S; McLure, R J; Carnall, A C; Begley, R; Cullen, F; Hamadouche, M L; Bowler, R A A; Magee, D; McCracken, H J; Milvang-Jensen, B; et al.
ABSTRACT: We reduce and analyse the available JWST ERO and ERS NIRCam imaging (SMACS0723, GLASS, CEERS) in combination with the latest deep ground-based near-infrared imaging in the COSMOS field (provided by UltraVISTA DR5) to produce a new measurement of the evolving galaxy UV luminosity function (LF) over the redshift range z = 8 − 15. This yields a new estimate of the evolution of UV luminosity density (ρUV ), and hence cosmic star formation rate density (ρSFR ) out to within <300 Myr of the Big Bang. Our results confirm that the high-redshift LF is best described by a double power law (rather than a Schechter) function up to z ∼ 10, and that the LF and the resulting derived ρUV (and thus ρSFR ), continues to decline gradually and steadily up to z ∼ 15 (as anticipated from previous studies which analysed the pre-existing data in a consistent manner to this study). We provide details of the 61 high-redshift galaxy candidates, 47 of which are new, that have enabled this new analysis. Our sample contains 6 galaxies at z ≥ 12, one of which appears to set a new redshift record as an apparently robust galaxy candidate at z ≃ 16.4, the properties of which we therefore consider in detail. The advances presented here emphasize the importance of achieving high dynamic range in studies of early galaxy evolution, and re-affirm the enormous potential of forthcoming larger JWST programmes to transform our understanding of the young Universe.